Work attendance anxiety, precarious work schedules, and job satisfaction of essential retail workers during the early COVID-19 pandemic - Hyeri Choi; Ioana Marinescu (PLoS ONE, 2025)
Building upon the Job Demands-Resources model, this study examines the relationships among precarious work schedules, work attendance anxiety, and employer support during the early COVID-19 pandemic. For part-time retail workers, the prevalence of precarious work schedules has been a persistent problem. Additionally, new challenges such as work attendance anxiety and lack of employer support emerged during the COVID-19 pandemic. Data were collected through an online survey on the Amazon Mechanical Turk platform. Between July and August 2020, we secured a sample of U.S. part-time workers in “food and beverage retail stores” (N = 179). Using Ordinary Least Squares regression analyses, we find that work attendance anxiety, lack of control over work hours, and non-standard working hours are negatively associated with job satisfaction. In terms of employer support, personal protective equipment is associated with lower levels of work attendance anxiety and alleviates the impact of work attendance anxiety on job satisfaction. The findings provide valuable insights for employers and managers aiming to enhance job satisfaction and effectively respond to challenges posed by health crises.